Assessment of the Balance of the Socio-Economic Development in the Regions (on the Example of the Volga Federal District of the Russian Federation): Methodology and Practice Analysis - SAFIULLIN, Marat Rashitovich; ELSHIN, Leonid Alekseevich; PRYGUNOVA, Mariya Igorevna (Journal of Advanced Research in Law and Economics; Vol 6 No 3 (2015): JARLE Volume VI, Issue 3(13), Winter 2015, 2017)
The analytical data opening efficiency of activity of executive authorities of subjects of the Volga Federal District on the basis of the carried-out complex assessment of separate private and integrated indicators are presented in article. The complex assessment of social and economic activity of regions is carried out on the basis of the analysis of two main components: development of the economic environment and development of the social sphere (Jacks and Safiullin 2011). The indicators characterizing the volume of private investments into fixed capital, the tax and non-tax income of the consolidated budget of the region, the real located monetary income of citizens, a turn of small business which values are defined counting on one inhabitant, and also the level of input of housing are carried to the block of development of economy (The report on a complex assessment of efficiency of activity of executive authorities of subjects of the Russian Federation following the results of 2013 year, 2014). The indicators characterizing the expected life expectancy, natural mortality, level of real unemployment, progress on the unified state examination and a share of the orphan children who aren't captured by various forms of the family device are carried to the block of social development. Measurement of the integrated summary indexes of development of the social and economic sphere forms idea of the main components defining a social and economic trend of the region. It, in turn, can and has to lay down in system of justification of priorities of regional development on average and long-term prospects.